2016
DOI: 10.1038/leu.2016.329
|View full text |Cite
|
Sign up to set email alerts
|

JUN is a key transcriptional regulator of the unfolded protein response in acute myeloid leukemia

Abstract: The transcription factor JUN is frequently overexpressed in multiple genetic sub-types of acute myeloid leukemia (AML), however, the functional role of JUN in AML is not well defined. Here we report that shRNA-mediated inhibition of JUN decreases AML cell survival and propagation in vivo. By performing RNA-seq analysis, we discovered that JUN inhibition reduces the transcriptional output of the Unfolded Protein Response (UPR), an intracellular signaling transduction network activated by endoplasmic reticulum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 61 publications
2
53
0
Order By: Relevance
“…Intriguingly, shRNA-mediated genetic ablation of XBP1 or ATF4 induced AML cell apoptosis and significantly extended disease latency in vivo in a murine model. Therefore, these findings tied the reduced AML cell survival observed when c-Jun activity was inhibited, to the loss of cytoprotective UPR signaling [106]. Moreover, the results identified the UPR as a promising potential therapeutic target in AML.…”
Section: Upr Involvement In Amlmentioning
confidence: 84%
See 1 more Smart Citation
“…Intriguingly, shRNA-mediated genetic ablation of XBP1 or ATF4 induced AML cell apoptosis and significantly extended disease latency in vivo in a murine model. Therefore, these findings tied the reduced AML cell survival observed when c-Jun activity was inhibited, to the loss of cytoprotective UPR signaling [106]. Moreover, the results identified the UPR as a promising potential therapeutic target in AML.…”
Section: Upr Involvement In Amlmentioning
confidence: 84%
“…c-Jun has been recently identified as a key transcriptional regulator of the UPR in AML. Indeed, upon ER stress induction, c-Jun is activated via mitogen-activated protein kinase kinase (MEK)/extracellular-regulated kinase (ERK) signaling and binds to the promoters of XBP1 and ATF4, thereby increasing their transcription and allowing leukemic cells to properly negotiate ER stress through cytoprotective UPR [106]. Of note, c-Jun/UPR signaling was activated by conventional chemotherapeutics (cytarabine, doxorubicine) used for AML patient treatment.…”
Section: Upr Involvement In Amlmentioning
confidence: 99%
“…The c-Jun oncogene is a member of the activator protein-1 (AP-1) family of transcription factors that is phosphorylated and activated by the JNK [51]. Previous study suggested that shRNAmediated inhibition of Jun decreased AML cell survival and propagation in vivo [52].…”
Section: Discussionmentioning
confidence: 99%
“…JUN encodes a virus-like protein, which regulates gene expression in response to cell stimulation by interacting directly with target DNA sequences. Several studies have shown that the transcription factor JUN is essential for neuronal microtubule assembly and apoptosis (Nateri et al 2004) and plays a very key regulatory role in the unfolded protein response in acute myeloid leukemia, which can serve as a promising therapeutic target in this disease (Zhou et al 2017). Recently, PPI analysis of AD and non-alcoholic fatty liver disease (NAFLD) has revealed that JUN is one of the hubbottleneck proteins in the PPI network and is an important target for both AD and NAFLD (Karbalaei et al 2018;Paquet et al 2017).…”
Section: Research Articlementioning
confidence: 99%